VD_FINDINFO HC / 2011 / 286 vom 20. April 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, MESURE PROVISIONNELLE | 137 al. 2 CC, 163 al. 1 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 314 al. 1 CPC (CH), 317 al. 1 CPC (CH)